O ônus da prova no processo administrativo sancionador - Silva, Marcelo Luís Abreu e (2018)
This academic work proposes to examine the development of probative activity in the punitive administrative procedure. The assumption is based on the submission of the public administrator to the constitutional guarantees granted to the accused in general. The duty to apply the sanction will find limits in the principle of presumption of innocence, serving as guidance for the practice of procedural acts in an attempt to prove the truth. In this way, the Public Administration will be respecting due process of law